Kehidupan Sosial Budaya Dan Sistem Kepercayaan Masyarakat Timur Tengah Kuno Pada Masa Abraham Dan Implikasi Bagi Kehidupan Kristen - Repi, Robby Robert; Phang, Steven (Perkumpulan Teolog Agama Kristen Indonesia, 2024)
The ancient civilization of Mesopotamia, particularly in the region between the Tigris and Euphrates rivers, is considered the cradle of early human civilization. This region greatly influenced the social, cultural, and belief systems that shaped the lives of its inhabitants, including Abraham, a key figure in the Bible. This study aims to explore the social, cultural, and religious practices in ancient Mesopotamia and how they influenced the life and decisions of Abraham, focusing on his family formation, societal roles, and spiritual journey. The study also seeks to highlight the implications of these ancient practices for modern Christian life. This research is a literature review, examining various books and scholarly articles to analyze the historical context of Mesopotamia during Abraham's time. The findings are synthesized and discussed to draw conclusions on the ongoing impact of these cultural and religious practices on modern Christianity. The research reveals that Abraham’s life and choices were deeply influenced by the cultural traditions of Mesopotamia, such as patriarchal family structures and spiritual beliefs. These ancient practices have continued to impact modern Christian family dynamics and the understanding of faith, particularly in terms of family leadership and obedience to God. Contribution: This article contributes by examining how Mesopotamian cultural and religious systems shaped Abraham’s life, offering insights into the historical roots of Christian family structures. It also highlights the ongoing relevance of these ancient practices in modern Christian teachings. Finally, it emphasizes the connection between Abraham’s journey and the development of Christian spiritual leadership. Peradaban kuno Mesopotamia, khususnya di wilayah antara Sungai Tigris dan Efrat, dianggap sebagai tempat lahirnya peradaban manusia awal. Wilayah ini sangat memengaruhi sistem sosial, budaya, dan kepercayaan yang membentuk kehidupan penghuninya, termasuk Abraham, seorang tokoh kunci dalam Alkitab. Penelitian ini bertujuan untuk mengeksplorasi praktik sosial, budaya, dan agama di Mesopotamia kuno serta bagaimana hal tersebut memengaruhi kehidupan dan keputusan Abraham, dengan fokus pada pembentukan keluarganya, peran sosial, dan perjalanan spiritualnya. Penelitian ini juga bertujuan untuk menyoroti implikasi praktik-praktik kuno ini terhadap kehidupan Kristen modern. Penelitian ini merupakan tinjauan pustaka, yang menganalisis berbagai buku dan artikel ilmiah untuk mengkaji konteks sejarah Mesopotamia pada masa Abraham. Temuan-temuan tersebut disintesis dan dibahas untuk menarik kesimpulan mengenai dampak berkelanjutan dari praktik budaya dan agama ini terhadap Kekristenan modern. Penelitian ini mengungkapkan bahwa kehidupan dan pilihan Abraham sangat dipengaruhi oleh tradisi budaya Mesopotamia, seperti struktur keluarga patriarkal dan kepercayaan spiritual. Praktik-praktik kuno ini terus memengaruhi dinamika keluarga Kristen modern dan pemahaman tentang iman, terutama dalam hal kepemimpinan keluarga dan ketaatan kepada Tuhan. Kontribusi: Artikel ini memberikan kontribusi dengan mengkaji bagaimana sistem budaya dan agama Mesopotamia membentuk kehidupan Abraham, memberikan wawasan tentang akar sejarah struktur keluarga Kristen. Artikel ini juga menyoroti relevansi berkelanjutan dari praktik-praktik kuno ini dalam ajaran Kristen modern. Akhirnya, artikel ini menekankan hubungan antara perjalanan Abraham dan perkembangan kepemimpinan spiritual Kristen.